Adapting to hurricanes. A historical perspective on New Orleans from its foundation to Hurricane Katrina, 1718–2005. (12th September 2017) - Rohland, Eleonora
Abstract : Recent policy debates on climate change have started highlighting the importance of adaptation of societies to new conditions projected by climate scientists. Previously, mitigation had been almost the sole focus of policy‐makers for fear of creating a moral hazard when concentrating more strongly on adaptation. Yet, with many of the climatic changes the Intergovernmental Panel on Climate Change (IPCC) projected occurring faster than scientists predicted, adaptation has re‐entered the debate as an imperative. In this context, in which adaptation—a process often unfolding on deep timescales—becomes prescriptive, it is crucial to look at the historical development of adaptive practices over the long term in order to appreciate the complexity of their evolution. This paper is a hybrid between a summary of a research project and a review of the most crucial literature on which it was based. The point of departure of this study was Hurricane Katrina, which, after it had flooded New Orleans on August 29, 2005, raised the question, how such a disaster could have happened in one of the most technologically advanced nations in the world. I then rewind to the foundation of the city in 1718 and work my way along case studies through three centuries of hurricane history in New Orleans. The red thread is the concept of adaptation. I review the definition of adaptation provided by the Fifth Assessment Report of the IPCC from a historian's point of view and suggest a slight change of perspective. Knowledge as a precondition for adaptation, contingency, path‐dependence, political vulnerability, and the interplay of cultural, legal, and political factors emerge as crucial characteristics in the historical evolution of adaptive practices throughout the almost 300‐year period of study. WIREs Clim Change 2018, 9:e488. doi: 10.1002/wcc.488 This article is categorized under: Climate, History, Society, Culture > World Historical Perspectives Abstract : Chronology of hurricanes and other extreme events that hit New Orleans during the 18th century ‐ the first and historically least researched period of this almost 300‐year study. Local/ indigenous knowledge as a precondition for adaptation, contingency, path‐dependence, political vulnerability, and the interplay of cultural legal, and political factors emerged as crucial characteristics in the historical evolution of adaptive practices in New Orleans.